Astrocyte and Glutamate Markers in the Superficial, Deep, and White Matter Layers of the Anterior Cingulate Gyrus in Schizophrenia - Katsel, Pavel (Nature Publishing Group, 2011)
Most studies of the neurobiology of schizophrenia have focused on neurotransmitter systems, their receptors, and downstream effectors. Recent evidence suggests that it is no longer tenable to consider neurons and their functions independently of the glia that interact with them. Although astrocytes have been viewed as harbingers of neuronal injury and CNS stress, their principal functions include maintenance of glutamate homeostasis and recycling, mediation of saltatory conduction, and even direct neurotransmission. Results of studies of astrocytes in schizophrenia have been variable, in part because of the assessment of single and not necessarily universal markers and/or assessment of non-discrete brain regions. We used laser capture microdissection to study three distinct partitions of the anterior cingulate gyrus (layers I–III, IV–VI, and the underlying white matter) in the brains of 18 well-characterized persons with schizophrenia and 21 unaffected comparison controls. We studied the mRNA expression of nine specific markers known to be localized to astrocytes. The expression of astrocyte markers was not altered in the superficial layers or the underlying white matter of the cingulate cortex of persons with schizophrenia. However, the expression of some astrocyte markers (diodinase type II, aquaporin-4, S100β, glutaminase, excitatory amino-acid transporter 2, and thrombospondin), but not of others (aldehyde dehydrogenase 1 family member L1, glial fibrillary acidic protein, and vimentin) was significantly reduced in the deep layers of the anterior cingulate gyrus. These findings suggest that a subset of astrocytes localized to specific cortical layers is adversely affected in schizophrenia and raise the possibility of glutamatergic dyshomeostasis in selected neuronal populations.